Behavior of Vibrio spp. in Table Olives - Posada-Izquierdo, Guiomar Denisse; Valero, Antonio; Arroyo-López, Francisco Noé; González-Serrano, Miriam; Ramos-Benítez, Alfonso M.; Benítez-Cabello, Antonio; Rodríguez-Gómez, Francisco; Jimenez-Diaz, Rufino; García-Gimeno, Rosa M. (Frontiers in Microbiology, 2021)
The presence of Vibrio species in table olive fermentations has been confirmed by molecular biology techniques in recent studies. However, there has been no report of any foodborne outbreak caused by Vibrio due to the consumption of table olives, and their role as well as the environmental conditions allowing their survival in table olives has not been elucidated so far. The aims of this work were to model the behavior of an inoculated Vibrio cocktail in diverse table olive environments and study the possible behavior of an inoculated Vibrio cocktail in table olives. First, an in vitro study has been performed where the microbial behavior of a Vibrio cocktail was evaluated in a laboratory medium and in olive brines using predictive models at different NaCl concentrations (2–12%) and pH levels (4.0–9.0). Afterward, a challenge testing was done in lye-treated olives inoculated at the beginning of fermentation with the Vibrio cocktail for 22 days. The Vibrio cocktail inoculated in table olives has not been detected in olive brines during fermentation at different pH levels. However, it was observed that this microorganism in a laboratory medium could reach an optimal growth at pH 9 and 2% salt, without time of constant absorbance (tA), and the maximum absorbance value (yend) observed was at pH 8 and 2% salt conditions. The statistical analysis demonstrated that the effect of salt concentration was higher than pH for the kinetic growth parameters (μmax, tA, and yend). On the other hand, it was confirmed that no growth of the Vibrio cocktail on any sample was noticed in lye-treated olive fermentations. Thus, it was concluded that the presence of olive compounds (unknown) did not allow the development of Vibrio strains, so it is a very safety product as it has a natural antimicrobial compound, but the possibility that a native Vibrio sp. is able to acquire the capacity to adapt to this compound should be considered in further studies.